(3eDGeQGJ fGaYI aj Yde GdWhH hGdbfHQIs
(3ChdgG (B:s
(3gPg eDGeQGJ fGaYI ai Yde GdWhH hGdbfHQI s
(3BNQgG (B:s
(3hgPg GdWQjbI de CSHb EdjgG ajeG CYde hGddg hdi GdJhajb s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B80) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs